KAJIAN PENGEMBANGAN EKOWISATA MANGROVE BERBASIS MASYARAKAT DI DESA POREANG KECAMATAN TANALILI KABUPATEN LUWU UTARA - Handri Suting; Hamsiah Hamsiah; Danial Danial (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2020)
The mangrove forest community has a unique and important role. Mangrove forests are very vulnerable to damage if the environment is not balanced, even the destruction of mangroves is not only caused by natural processes, but also due to human activities, it needs direction and solutions in sustainable mangrove management. One of the efforts made in sustainable marine management is the development of community-based mangrove tourism potential. The purpose of this research (1) Evaluate social, economic and ecological empowerment, (2) Determine community empowerment strategies through mangrove ecotourism. Data collection instruments were carried out using questionnaires and field observation, then analyzed descriptively and then analyzed using a SWOT analyst. Based on the research conducted, it is found that the achievements of social, economic and ecological empowerment in the tourism area have not been achieved. And to achieve this success there are 3 strategic directions that are carried out in the development of community-based ecotourism (1) Development of community-based mangrove ecotourism with the assistance of institutions and government (2) Conduct training and development of local products and community skills to support mangrove forest ecotourism (3) Increasing socialization and community involvement in planning